Structural absorption by barbule microstructures of super black bird of paradise feathers - Dakota E. McCoy (Nature Portfolio, 2018)
Physical structure is known to contribute to the appearance of bird plumage through structural color and specular reflection. Here, McCoy, Feo, and colleagues demonstrate how a third mechanism, structural absorption, leads to low reflectance and super black color in birds of paradise feathers.